2019
DOI: 10.1073/pnas.1816456116
|View full text |Cite
|
Sign up to set email alerts
|

REM sleep’s unique associations with corticosterone regulation, apoptotic pathways, and behavior in chronic stress in mice

Abstract: One of sleep’s putative functions is mediation of adaptation to waking experiences. Chronic stress is a common waking experience; however, which specific aspect of sleep is most responsive, and how sleep changes relate to behavioral disturbances and molecular correlates remain unknown. We quantified sleep, physical, endocrine, and behavioral variables, as well as the brain and blood transcriptome in mice exposed to 9 weeks of unpredictable chronic mild stress (UCMS). Comparing 46 phenotypic variables revealed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 84 publications
(106 reference statements)
2
57
0
1
Order By: Relevance
“…At this time, the mechanism for REM sleep regulation through Arc is unclear. It might be related to the phenomenon that "stress" tends to increase REM sleep (33,34). Further studies are required to elucidate the Arc-mediated regulation of REM sleep.…”
Section: Discussionmentioning
confidence: 99%
“…At this time, the mechanism for REM sleep regulation through Arc is unclear. It might be related to the phenomenon that "stress" tends to increase REM sleep (33,34). Further studies are required to elucidate the Arc-mediated regulation of REM sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in sleep time have been shown to be associated with higher reported stress levels the next day [82]. Conversely, chronic stress has been associated with reduced time spent in REM sleep [83,84]. Early life stress is associated with insomnia [85,86] and can result in increased serum concentrations of inflammatory cytokines [14,57,87].…”
Section: Stress and Periodontitis: The Sleep Connectionmentioning
confidence: 99%
“…In the other mouse SDS model [Henderson et al, 2017], REM sleep durations and bouts decreased and REM sleep theta power remained unchanged during the light phase. In the UCMS model [Nollet et al, 2019], REM sleep duration, bouts, and theta power (per day) increased during the 9-week UCMS. In the WIRS model [Yasugaki et al, 2019], REM sleep duration and bouts during the dark phase increased during the first week of the stress episode.…”
Section: Discussionmentioning
confidence: 91%
“…A pioneering study by Hegde et al investigated the effects of 2-hr chronic immobilization stress (CIS) for 10 days on REM sleep theta oscillation and found that a subgroup of stressed rats showed increased REM sleep durations in association with attenuated REM sleep theta powers [Hegde et al, 2011]. Recently, four independent studies, using mouse SDS [Wells et al, 2017;Henderson et al, 2017], unpredictable chronic mild stress (UCMS) [Nollet et al, 2019], and water immersion and restraint stress (WIRS) [Yasugaki et al, 2019] models, have shown that these stresses induced changes in various REM sleep parameters. These changes, however, were observed mostly during the stress periods and little was observed in terms of post-stress effects (only 5 days after the last SDS [Wells et al, 2017;Henderson et al, 2017]).…”
Section: Discussionmentioning
confidence: 99%